Anterior Cruciate Ligament Return to Play: Where Are We Now? - Oladeji, Lasun; Reynolds, Grace; Gonzales, Hyeri; DeFroda, Steven (The Journal of Knee Surgery, 2023)
Anterior cruciate ligament reconstruction (ACLR) is a commonly performed orthopaedic procedure, and it is crucial to assess an athlete's readiness to safely return to sports following ACLR to minimize the risk of reinjury. Despite this, determining optimal return to play (RTP) criteria following ACLR that is accurate, accessible, and reproducible remains challenging. This review aims to discuss commonly employed RTP criteria domains, including functional assessments, patient-reported outcomes, and psychological tests, as well as emerging technologies such as magnetic resonance imaging (MRI) that may play a role as a gold standard in RTP assessment. The findings of this review suggest RTP decision making after ACL surgery is nuanced and traditionally used objective measures do not perfectly predict RTS rates or clinical outcomes. In the future, a standardized MRI screening tool could help predict reinjury. The role of functional and psychological patient-reported outcome measures needs to defined, and objective criteria should be rigorously evaluated for whether they accurately screen an athlete's physical readiness and should be expanded to include more sport-specific movement analysis.
Keywords: knee; ACL; return to play; outcomes